2004
DOI: 10.1029/2003jc002179
|View full text |Cite
|
Sign up to set email alerts
|

A gap in the Indo‐Pacific warm pool over the South China Sea in boreal winter: Seasonal development and interannual variability

Abstract: [1] The Indo-Pacific warm water pool in boreal winter shows a conspicuous gap over the South China Sea (SCS) where sea surface temperature (SST) is considerably lower than over the oceans both to the west and east. The formation mechanisms for the climatology and interannual variability of SCS SST in boreal winter are investigated using a suite of new satellite measurements. The winter SCS is divided into two parts by the axis of the maximum northeasterly monsoonal winds. The positive wind curl in the southeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 30 publications
(48 reference statements)
5
151
0
3
Order By: Relevance
“…h , implying the divergence and convergence of eddy energy, exist along the eastern and western side of the southwestward horizontal current which may be caused by advection [Liu et al, 2004]. Compared with the abovementioned terms, tendency of EKE is small (Figure 4e), while the turbulent processes acts as the main sinks of the eddy energy with high values at southwestern SCS and the Luzon Strait (Figure 4f).…”
Section: Eddy Energy Sources and Sinksmentioning
confidence: 96%
“…h , implying the divergence and convergence of eddy energy, exist along the eastern and western side of the southwestward horizontal current which may be caused by advection [Liu et al, 2004]. Compared with the abovementioned terms, tendency of EKE is small (Figure 4e), while the turbulent processes acts as the main sinks of the eddy energy with high values at southwestern SCS and the Luzon Strait (Figure 4f).…”
Section: Eddy Energy Sources and Sinksmentioning
confidence: 96%
“…The impact of topography on the SCS summer climate characteristics was further validated by a model [86]. There exists a summer cold tongue in the temperature structure associated with the SCSWBC; in addition, there is still a significant cold tongue in the same region in winter, and the generation of the winter cold tongue is related to the southward cold advection by the SCSWBC [87]. Xie et al [88] found that the 30-60 day intraseasonal oscillation of SST associated with the SCSWBC was under the influence of the Vietnam coastal upwelling [67,68], and this intraseasonal oscillation amplitude was obviously more significant near Vietnam coast than in any other regions.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…It is well-known that the cold tongue is caused by the winter monsoon, both directly through enhanced upward heat fluxes from strong surface wind and indirectly through cold water advection due to the western boundary current off the coast of Vietnam (Liu et al, 2004) set up by the monsoon. But, does the cold tongue have any impact on the winter monsoon itself and the associated rainfall in the Maritime Continent?…”
Section: Introductionmentioning
confidence: 99%
“…Centurioni et al (2009) estimated that the significant strength of Ekman currents off Vietnam is associated with the wind stress curl in the winter monsoon season. Liu et al (2004) showed that the western boundary current (e.g. Stommel, 1948) along the Vietnam coast transports colder seawater southward and forms the so-called cold tongue, an extension of cool sea surface temperature (SST) in SCS, which at the coldest is about 298 K. The cold tongue starts to form in November and lasts until March (Chen et al, 2003) before disappearing in April.…”
Section: Introductionmentioning
confidence: 99%